2014
DOI: 10.1080/09168451.2014.882747
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative activity of 6-O-acyl-d-allose against the human leukemia MOLT-4F cell line

Abstract: The anti-proliferative activities of the 6-O-acyl derivatives of d-allose against the human leukemia MOLT-4F cell line were examined. The activity of the 6-O-dodecanoyl derivative (3) was approximately 30 times stronger than that of d-allose. An evaluation of the derivatives of 3 that occurred in a furanose form revealed the pyranose forms of 3 to be important for the anti-proliferative activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The experiments carried out on both in vitro and in vivo cell models confirm that SFAE may inhibit the secretion of TNF-α and some proinflammatory cytokines such as IL-1B, IL-6 and IL-8 [17]. Moreover, their ability to inhibit in vitro excessive proliferation of bone marrow cells in the acute myelogenous leukemia model was also described [18]. It has also been shown that biological activity of SFAE may depend on the length of an aliphatic chain and their number in the whole ester molecule (mono-vs. di-vs. tri-/poly-esters).…”
Section: Introductionmentioning
confidence: 65%
“…The experiments carried out on both in vitro and in vivo cell models confirm that SFAE may inhibit the secretion of TNF-α and some proinflammatory cytokines such as IL-1B, IL-6 and IL-8 [17]. Moreover, their ability to inhibit in vitro excessive proliferation of bone marrow cells in the acute myelogenous leukemia model was also described [18]. It has also been shown that biological activity of SFAE may depend on the length of an aliphatic chain and their number in the whole ester molecule (mono-vs. di-vs. tri-/poly-esters).…”
Section: Introductionmentioning
confidence: 65%